A novel metalloprotease from Bacillus cereus for protein fibre processing - Sousa, Fernanda (2007)
A novel protease produced by Bacillus cereus grown on wool as carbon and nitrogen source was purified. B. cereus protease is a neutral metalloprotease with a molecular mass of 45.6 kDa. The optimum activity was at 45 °C and pH 7.0. The substrate specificity was assessed using oxidized insulin B-chain and synthetic peptide substrates. The cleavage of the insulin B-chain was determined to be Asn3, Leu6, His10-Leu11, Ala14, Glu21, after 12 h incubation. Among the peptide substrates, the enzyme did not exhibit activity towards ester substrates; with p-nitroanilide, the kinetic data indicate that aliphatic and aromatic amino acids were the preferred residues at the P1 position. For furylacryloyl peptides substrates, which are typical substrates for thermolysin, the enzyme exhibited high hydrolytic activity with a Km values of 0.858 and 2.363 mM for N-(3-[2-Furyl]acryloyl)-Ala-Phe amide and N-(3-[2-Furyl]acryloyl)-Gly-Leu amide, respectively. The purified protease hydrolysed proteins substrates such as azocasein, azocoll, keratin azure and wool.